A behavioral view on chimpanzee personality: Exploration tendency, persistence, boldness, and tool‐orientation measured with group experiments. Issue 9 (3rd May 2013) - Massen, Jorg J.M.; Antonides, Alexandra; Arnold, Anne‐Marie K.; Bionda, Thomas; Koski, Sonja E.
Abstract Human and nonhuman animals show personality: temporal and contextual consistency in behavior patterns that vary among individuals. In contrast to most other species, personality of chimpanzees, Pan troglodytes, has mainly been studied with non‐behavioral methods. We examined boldness, exploration tendency, persistence and tool‐orientation in 29 captive chimpanzees using repeated experiments conducted in an ecologically valid social setting. High temporal repeatability and contextual consistency in all these traits indicated they reflected personality. In addition, Principal Component Analysis revealed two independent syndromes, labeled exploration‐persistence and boldness. We found no sex or rank differences in the trait scores, but the scores declined with age. Nonetheless, there was considerable inter‐individual variation within age‐classes, suggesting that behavior was not merely determined by age but also by dispositional effects. In conclusion, our study complements earlier rating studies and adds new traits to the chimpanzee personality, thereby supporting the existence of multiple personality traits among chimpanzees. We stress the importance of ecologically valid behavioral research to assess multiple personality traits and their association, as it allows inclusion of ape studies in the comparison of personality structures across species studied behaviorally, and furthers our attempts to unravel the causes and consequences of animal personality. Am. J. Primatol. 75:947–958, 2013. © 2013 Wiley Periodicals, Inc.